2018
DOI: 10.3389/fneur.2018.00196
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Related Concussion Alters Indices of Dynamic Cerebral Autoregulation

Abstract: Sport-related concussion is known to affect a variety of brain functions. However, the impact of this brain injury on cerebral autoregulation (CA) is poorly understood. Thus, the goal of the current study was to determine the acute and cumulative effects of sport-related concussion on indices of dynamic CA. Toward this end, 179 elite, junior-level (age 19.6 ± 1.5 years) contact sport (ice hockey, American football) athletes were recruited for preseason testing, 42 with zero prior concussions and 31 with three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 69 publications
0
62
1
Order By: Relevance
“…Increasingly, the rich sympathetic innervation of the cerebrovascular tree is recognized to play an important role in the dynamic regulation of BP variability ( 37 ). Numerous lines of evidence have outlined the detrimental effects of concussion on autonomic function ( 20 ) including systematic alterations in dCA ( 21 ). In the current study, disruptions were observed in both the latency and magnitude of the dCA response following subconcussive head impacts, indicating even mild repetitive head impacts are associated with disruptions to CBF regulation during BP challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly, the rich sympathetic innervation of the cerebrovascular tree is recognized to play an important role in the dynamic regulation of BP variability ( 37 ). Numerous lines of evidence have outlined the detrimental effects of concussion on autonomic function ( 20 ) including systematic alterations in dCA ( 21 ). In the current study, disruptions were observed in both the latency and magnitude of the dCA response following subconcussive head impacts, indicating even mild repetitive head impacts are associated with disruptions to CBF regulation during BP challenges.…”
Section: Discussionmentioning
confidence: 99%
“…An additional 109 contact sport participants did not complete post-season testing for one of the following reasons: (i) traded to a team in a different city, (ii) returned to their hometown immediately following the end of the season, (iii) unable to attend a testing session within 2-weeks of season's end, or (iv) injury preventing the completion of testing. The remaining 18 contact sport athletes were diagnosed by team physicians and medical staff with a concussion during the season based on criteria outlined in the 4th Consensus Statement ( 24 ) and followed a different post-injury protocol that has been reported in a recent publication ( 21 ). Although the number of control subjects is relatively low, the differences we observed in the current study are larger than the within-subject coefficients of variation for dCA measures (10–15%) reported for healthy participants by our group ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three major limitations to these previous studies: (a) only the short‐term effects of CA during exercise or within 60 min of exercise cessation were examined; the duration of dynamic CA alterations postexercise remain unknown; (b) only two studies have examined the CA relationship across the cardiac cycle (Ogoh, Fadel, et al, ; Ogoh, Fisher, et al, ); as recent research has shown each phase of the cardiac cycle responds differently to a given stimulus, examining the mean may not accurately portray important subtleties between diastolic and systolic components (Smirl, Wright, Ainslie, Tzeng, & Donkelaar, ; Wright, Smirl, Bryk, & Donkelaar, ); and (c) only one of these prior studies employed a research method (oscillatory lower body negative pressure during the exercise intervention) which evoked sufficient coherence to provide reproducible interpretations of the associated phase and gain metrics (Smirl, Hoffman, Tzeng, Hansen, & Ainslie, ). Moreover, recent research has demonstrated when squat–stand maneuvers are employed to quantify CA parameters, coherence values are enhanced to near linear levels (~0.99) (Kostoglou et al, ; Smirl, Haykowsky, et al, ; Smirl et al, , , ; Smirl, Lucas, et al, ; Smirl, Tzeng, Monteleone, & Ainslie, ; Wright, Smirl, Bryk, & Donkelaar, ; Wright et al, , ). This methodological approach leads to greater reproducibility within the CA outcome measures (phase, absolute gain, and normalized gain) (Claassen et al, ; Smirl et al, ), which will enhance the interpretability and application of the findings related to the current investigation.…”
Section: Introductionmentioning
confidence: 99%
“…This evolving research that has examined the pathophysiology of concussion, includes monitoring cerebral blood flow velocity using transcranial Doppler (Len et al, 2011;Wright et al, 2018), cerebral blood-oxygen-level-dependent (BOLD) changes using functional magnetic resonance imaging (fMRI; Mutch et al, 2014Mutch et al, , 2018, blood pressure (La Fountaine et al, 2016Bishop et al, 2017b;Wright et al, 2018), heart rate variability (HRV; Gall et al, 2004;La Fountaine et al, 2009;Bishop et al, 2017a,b), cortical activation (Pearce et al, 2019), and cerebral hemodynamics using near-infrared spectroscopy (Urban et al, 2015;Bishop and Neary, 2017). In particular, near-infrared spectroscopy (NIRS) is an optical technique that has been validated to show quantitative changes in blood volume (an indirect measure of blood flow velocity) and oxygenation in cerebral tissue (Ferrari et al, 2004;Bhambhani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%